AGE-STRATIFIED PREVALENCE AND ANTIBIOTIC RESISTANCE PATTERNS OF HELICOBACTER PYLORI INFECTION AMONG PATIENTS UNDERGOING UPPER GASTROINTESTINAL ENDOSCOPY IN A TERTIARY CARE HOSPITAL, INDIA - Ahmad, Imtiyaz; Hassan, Syed Belal; Mustaqueem, Syed Fiza; Ahmad, Ausaf (Journal of Global Pharma Technology, 2024)
The infection rate of H. pylori varies significantly between developing and developed nations, with rates approximately four to five times higher in developing countries. Antibiotic misuse has contributed to resistance issues, complicating eradication efforts. Study aimed to assess age-specific H. pylori prevalence and antibiotic resistance among patients undergoing Upper Gastrointestinal Endoscopy at a tertiary care hospital in India. Study included patients aged 14 to 86 presenting with symptoms like dyspepsia and epigastric pain. Demographic data and treatment history were collected, excluding recent antibiotic or proton pump inhibitor users. Statistical analysis was performed using SPSS version 16.0. Results indicated an overall prevalence of 61.1%, with similar rates across genders. Infection rates peaked at 73.7% in patients above 70 years. Positive endoscopic findings correlated significantly with H. pylori infection, underlining the importance of endoscopic evaluations. Notably, symptoms like epigastric pain were linked to H. pylori positivity. The study concluded that H. pylori prevalence is notably high in individuals above 70 years old. Additionally, it shed light on gender-specific prevalence patterns and highlighted metronidazole resistance as the most common, followed by levofloxacin and amoxicillin resistance. Furthermore, the study stressed the importance of endoscopic examinations in diagnosing H. pylori infection. Keywords: Antibiotic Resistance, Dyspepsia, Epigastric pain, H. pylori, Prevalence.